Analiza wybranych zmian wprowadzonych na mocy Polskiego Ładu w zakresie tworzenia i funkcjonowania podatkowych grup kapitałowych - Katarzyna Błaszczak (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The article is devoted to the analysis of selected changes related to the creation and functioning of tax capital groups, introduced under the law referred to as the “Polish Deal.” The intention of the Polish legislator was to increase interest in tax capital groups and to create opportunities for smaller entrepreneurs to join them. To this end, among other things, it was decided, the formal conditions for joining these structures were liberalized, the obligation to maintain the profitability of the group was dropped, and the prohibition on making changes to the composition of the companies forming the tax capital group was repealed. The article provides an assessment of the most significant changes that came into effect on January 1, 2022, and their impact on the actual interest in creating tax capital groups.